Upregulation of Fibrinogen-Like 1 Expression Contributes to Reducing the Progression of Preeclampsia - Cheng, Tsung-Lin; Chen, Chung-Hwan; Wu, Meng-Hsing; Lai, Chao-Han; Lee, Ko-Hung; Lin, Sheng-Hsiang; Shiau, Ai-Li; Wu, Chao-Liang; Kang, Lin (Frontiers in Cell and Developmental Biology, 2021)
Fibrinogen-like 1 (FGL1) is involved in liver injury and liver regeneration, but its role in placenta and preeclampsia (PE) remains unclear. We assessed FGL1 expression in serum and placenta from L-NAME-induced PE-like mouse and in women with (n=38) and without (n=42) PE. For the mouse study, pregnant C57Bl/6 mouse (n=6/group) were subcutaneously administered L-NAME with or without FGL1 once daily starting on days 7–14 of pregnancy and were sacrificed on gestational day (GD) 20. Maternal body weight, blood pressure, and urinary protein were assessed during GDs 8–20. The weight and length of the placenta and fetus were assessed. The placental structure was evaluated using hematoxylin staining. In the human study, the sera of the pregnant women during the late trimester were assessed with enzyme-linked immunosorbent assays (ELISAs). FGL1 expression in human trophoblast cell lines under L-NAME stimulation was measured using Western blotting and immunofluorescence staining. The detected FGL1 protein levels in serum and placenta were both significantly upregulated in patients and mouse with PE compared with those in the non-PE groups. FGL1 treatment decreased maternal hypertension and proteinuria, decreased fetal weight in mouse with PE, downregulated proinflammatory cytokine (interleukin-1b and interleukin-6) levels, and maintained the balance between antiangiogenic (fms-like tyrosine kinase-1) and proangiogenic (placental growth factor) substances in the placenta. L-NAME-upregulated FGL1 expression was inhibited following overexpression of FoxO3a. In summary, FoxO3a reduction is a potential pathophysiological mechanism leading to upregulated placental FGL1 expression that may play a pivotal role in preventing PE progression.